The (non) acceptance of Fundação Casa in São Paulo’s municipalities: na analysis in the light of direct actions of unconstitutionality - Pires de Borba, Jadir; Levy Braga da Silva Neto, Wilson (Revista da Faculdade de Direito do Sul de Minas, 2021)
The Statute of the Child and Adolescent (ECA) and the National System of Socioeducative Support Law (SINASE) establish the importance of the territorial integration of service centers in the execution of socio-educational measures, however, many municipalities are still resistant to the establishment of custody and semi-liberty facilities in their territories. This article seeks to study this movement aimed to prevent or limit the establishment of such facilities, based on the analysis of Direct Actions of Unconstitutionality sought by the states. The results of the research note the movement of the municipalities in order to prevent these facilities at the beginning of the decentralization process, as carried out, at first in the late 1990s and, secondly, from 2005 on. Jurisprudence from the Brazilian Judicial Power was found, in the sense that such practices consist of usurpation of competence belonging to the states and the Union, under the terms of the Constitution of the State of São Paulo and the Federal Constitution.